ANALISIS FAKTOR–FAKTOR FUNDAMENTAL TERHADAP RETURN SAHAM PADA PERUSAHAN PHARMACEUTICALS DI BURSA EFEK INDONESIA PERIODE 2018-2021 - Nanang Asfufi (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2023)
The purpose of this study is to analyze the effect of Debt to Equity Ratio (DER), Current Ratio (CR), Return On Assets (ROA), Debt to Assets Ratio (DAR) on stock returns and simultaneously affect stock returns of a company: Since 2018 until 2021, which is listed as active on the Indonesia Stock Exchange. The sample used is pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling with criteria. The research method used is multiple linear regression. The results of the study show that the current ratio variable partially has a significant effect on stock returns while the debt to equity ratio, return on assets, debt to assets ratio partially does not have a significant effect on stock returns. conversely, if the use of the current ratio, debt to equity ratio, return on assets, and debt to assets ratio simultaneously or simultaneously has a significant effect on stock returns.